(untitled) (Journal of the College of Basic Education, 2026)
The research aimed to identify: moral violations among university students, and the significance of the difference in moral violations according to the variable of specialization (scientific, humanities). To achieve the research objectives, the researchers constructed a moral violation scale, consisting of (30) items distributed over three areas: contradiction to societal standards, consisting of (10) items; displacement of responsibility, consisting of (10) items; and social rules, consisting of (10) items, with a five-point scale (always, often, sometimes, rarely, never), (1, 2, 3, 4, 5). The properties of ten items were verified, as the scale was applied to a sample of (100) students who were randomly selected to extract the study results. The research results showed that the individuals in the research sample had moral violations, according to the hypothetical mean. There were no statistically significant differences in Ethical violation according to the variable of specialization (scientific, humanities), and in light of the results, the researchers presented a number of recommendations and proposals.